Clinical utility of the solid meal test during high-resolution esophageal manometry. A study in a Latin American population - K.R. García-Zermeño; J. Argüero; M. Amieva-Balmori; O. Rodríguez-Aguilera; A. Martínez-Conejo; M. Marcolongo; J.M. Remes-Troche (Revista de Gastroenterología de México (English Edition))
Introduction and aims: The solid test meal (STM) is a challenge test that is done during esophageal manometry and appears to increase the diagnostic yield of the study. The aim of our analysis was to establish the normal values for STM and evaluate its clinical utility in a group of Latin American patients with esophageal disorders versus healthy controls. Material and methods: A cross-sectional study was conducted on a group of healthy controls and consecutive patients that underwent high-resolution esophageal manometry, in which STM was done at the final part of the study and consisted of asking the subjects to eat 200 g of precooked rice. The results were compared during the conventional protocol and the STM. Results: Twenty-five controls and 93 patients were evaluated. The majority of the controls (92%) completed the test in under 8 min. The STM changed the manometric diagnosis in 38% of the cases. The STM diagnosed 21% more major motor disorders than the conventional protocol; it doubled the cases of esophageal spasm and quadrupled the cases of jackhammer esophagus, whereas it demonstrated normal esophageal peristalsis in 43% of the cases with a previous diagnosis of ineffective esophageal motility. Conclusions: Our study confirms the fact that complementary STM during esophageal manometry adds information and enables a more physiologic assessment of esophageal motor function to be made, compared with liquid swallows, in patients with esophageal motor disorders. Resumen: Introducción y objetivos: La prueba con comida sólida (PCS) es una prueba de provocación que se realiza durante una manometría esofágica y al parecer incrementa el rendimiento diagnóstico de ésta. El objetivo de este estudio fue establecer los valores de normalidad de la PCS y evaluar su utilidad clínica en un grupo de pacientes hispanos con trastornos esofágicos y controles sanos. Material y métodos: Se realizó un estudio transversal en un grupo de controles sanos y pacientes consecutivos que fueron sometidos a una manometría esofágica de alta resolución, donde al final se realizó la PCS que consistió en pedirles que comieran 200 gramos de arroz precocido. Se compararon los resultados obtenidos durante el protocolo convencional y la PCS. Resultados: Se evaluaron 25 controles y 93 pacientes. La mayoría de los controles (92%) completaron la prueba en un tiempo menor de 8 minutos. La PCS cambió el diagnóstico manométrico en el 38% de los casos. La PCS diagnosticó 21% más trastornos motores mayores que el protocolo convencional, en especial se duplicaron los casos de espasmo esofágico y se cuadruplicaron los casos de esófago en martillo neumático. Por otro lado, la PCS demostró una peristalsis esofágica normal en 43% de los casos con diagnóstico previo de motilidad esofágica inefectiva. Conclusiones: Nuestro estudio confirma que la realización de una PCS complementaria durante el protocolo de manometría esofágica añade información y permite una evaluación más fisiológica de la función motora esofágica en comparación con las degluciones líquidas en pacientes con trastornos motores del esófago.